Estresse oxidativo em cães com doença renal crônica - Galvão, André Luiz Baptista [UNESP] (2014)
The establishment of oxidative stress results from an imbalance between oxidants and antioxidants compounds, which generates accumulation of reactive oxygen species (ROS). Studies conducted in terminal stages of chronic kidney disease (CKD) in humans and mice demonstrated an increase in ROS generation. The aim of this study was to determine if the same pattern of response occurs in dogs clinically stable at different stages of naturally occurring CKD. The experimental protocol of this study was previously approved by the Ethics Committee on the use of Animals n.° 013690/11. Five groups of dogs, all aged between four to 18 years old. Were studied the control group was composed of healthy animals (CG, n = 17), CKD stage 1 group (CKD-1, n = 12), CKD stage 2 group (CKD-2, n = 10), CKD stage 3 group (CKD-3, n = 13) and CKD stage 4 group (CKD-4, n = 10). CKD dogs were clinically stable with no treatment. Two blood samples were collected at intervals of 24 hours (repeated measures) to obtain serum and plasma. Oxidative stress was measured by antioxidant power and indirectly by determination of nitric oxide (NO) by nitrate/nitrite. Data (means of duplicates) were submitted to analysis of variance (One-way ANOVA) nonparametric (Kruskal-Wallis) (α = .05). The results were expressed as mean±standard error of the mean. The serum creatinine values guided the classification of patients as CG, CKD-1, CKD-2, CKD-3 and CKD-4 and were 1.02±0.02mg/dL, 1.06±0.05 mg/dL, 1.80±0.03 mg/dL, 3.39±0.21 mg/dL and 6.00±0.28 mg/dL, respectively. The results related to antioxidant power (GC) 0.032 ± 0.002 mmol/μL, (CKD-1) 0.030±0.002nmol/μL, (CKD-2) 0.028±0.003nmol/μL, (CKD- 3) 0.027±0.003 nmol/μL and (CKD-4) 0.025 ± 0.002 nmol/μL were different between the healthy dogs and dogs with CKD, but not differ significantly among groups. The results of the NO plasma concentrations did not differ significantly when comparing the GC data (10.81±0.51μM) ...